PENGEMBANGAN VIRTUAL REALITY SITUS SEJARAH KOTA SINGKAWANG SEBAGAI MEDIA PEMBELAJARAN SEJARAH LOKAL - Chalimi, Ika Rahmatika (Universitas Tanjungpura, 2025)
The development of Virtual Reality (VR) as an educational media for local history in Singkawang City aims to enhance history teaching and learning. This study addresses challenges in history education, such as limited resources and lack of interactivity in traditional methods. Virtual reality provides an innovative solution by allowing students to explore historical sites in Singkawang virtually, enriching their understanding through immersive experiences. This method increases student interest and engagement while helping them appreciate Singkawang's historical and cultural heritage. Using the ADDIE model, the research highlights the design and initial evaluation of virtual reality content focused on historical sites in Singkawang City. Early responses from students and educators show a positive impact on learning outcomes, highlighting virtual reality